Nisab of Zakat and Zakat Contribution: A Conceptual Model - Azhan Rashid Senawi; Heizal Hezry Omar; Amirul Afif Muhamat; Shariff Harun; Husna Husain; Tika Widiastuti; Nazri Chik (Information Management and Business Review, 2023)
Zakat distribution has a positive correlation with its collection. Thus, a higher collection of zakat will positively impact the distribution amount and reach a bigger pool of zakat recipients. However, some external constraints in its collection could likely have an adverse impact on its collection, especially the effect of the macroeconomic factors. It becomes crucial when the increase in the price of gold (one of the primary commodities used as a nisab benchmark for zakat in Islam) is claimed to negatively influence the collection and allocation of zakat to the respective recipients. Therefore, this study aims to investigate whether the high and low value of nisab due to the fluctuating price of gold in the world market could negatively influence the zakat collection and indirectly affect all the recipients, especially the poor and needy. In achieving this aim, this study will utilize a structured self-administered questionnaire to study the awareness of Muslims on the nisab of zakat and its influence on their zakat payments. It is still relatively rare to find any research on the awareness of the nisab of zakat and its relation to the zakat contribution. One past econometric study concluded that a higher nisab leads to a lower zakat collection. The findings of this proposed study could complement that previous study and hence be justifiable due to its significant impact on the recipients of zakat (asnaf) as the main stakeholders.